PENGARUH MOTIVASI, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK BTPN Tbk DI KANTOR CABANG LAMONGAN - Kemal Farouq M; Randi Bachtiar Afandi; Abdul Ghofur Zulkifli Lubis; Ratna Ekasari (IQTISHADequity jurnal MANAJEMEN, 2022)
This study aims to determine the effect of motivation and work discipline on employee performance at PT. Bank BTPN Tbk at the Lamongan Branch Office. This type of research, namely quantitative. Several variables that are connected in this study are the variable of motivation (X1), work discipline (X2), and employee performance (Y). The type of data used is primary data. Primary data is data obtained directly from respondents. The analysis technique of this research uses multiple linear regression analysis technique with the same population and sample, namely 50 people. The results obtained from this study are that motivation and work discipline have a positive and significant effect simultaneously and partially on employee performance at PT. Bank BTPN Tbk at the Lamongan Branch Office